In-Structure Shock of Surface Structures: A Theoretical Approach - Hongyuan Zhou; Xiaojuan Wang (Shock and Vibration)
Metal foam cladding emerges as a promising measure for structure protection against close range blast. With proper cladding design, a considerable amount of energy can be absorbed while the load transmitted to the protected structure can be lowered to a controllable level, leading to less damage of the protected structure. However, it is not clear whether the in-structure shock can be mitigated by attaching foam cladding. The present study theoretically investigates the response of a structural member subjected to a close range blast, for both scenarios with and without attaching foam cladding. Subsequently, shock response spectra are employed to assess the in-structure shock of both situations. It is found that applying foam cladding does not effectively mitigate in-structure shock of surface structures.